Transformational Leadership Style, Work Discipline, Work Stress, and Work Motivation: Their Influence on Employee Performance RSU Purbowangi Kebumen - Susanti, Riska Dwi; Aryoko, Yudhistira Pradipta; Widhiandono, Hengky; Hidayah, Arini (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this study is to explore the impact of transformational leadership style, level of work discipline, level of work stress, and level of work motivation on employee performance at Purbowangi General Hospital. A total of 100 employees working in this hospital were respondents in this study, and data were collected using the census method. The results revealed that multiple linear regression analysis indicated that transformational leadership style (β=7.534, significance=0.003), work discipline (β=6.423, significance=0.004), work stress (β=5.174, significance=0.005), and work motivation (β=7.727, significance=0.003) had a significant influence on employee performance. These findings suggest that in the context of employee performance in hospitals, all four factors have a significant impact. The study contributes by combining transformational leadership style, work discipline, work stress, and work motivation in the context of employee performance in hospitals. It also adds new insights to theoretical analysis, resulting in important findings to enhance performance.